Balancing Faith and Fairness: A Maqāṣid al-Sharīʻah Perspective on Regulating Repeated Hajj in Indonesia - Husen, Fathurrohman; Mukhlishin (Fakultas Syariah, Universitas Islam Negeri Raden Mas Said Surakarta, 2024)
This study explores the phenomenon of repeated Hajj through the perspective of maqāṣid al-sharīʻah (the objectives of Islamic law), focusing on its social, economic, and spiritual implications. Employing a juridical approach enriched with maqāṣid analysis, the research examines Islamic legal texts, government regulations, and empirical data concerning the implementation of Hajj in Indonesia. The findings categorize repeated Hajj as makruh litanzih (discouraged) due to its adverse effects, such as extended waiting times, economic inefficiencies, and heightened health risks for elderly pilgrims. Notably, over 60% of Indonesian Hajj pilgrims are above 60 years old, with waiting periods spanning 20 to 40 years in some regions. This study advocates redirecting financial resources toward supporting others' Hajj, a practice more aligned with maqāṣid principles by prioritizing public welfare (maslahah). It underscores the need for stricter regulations, greater public awareness of contextual Hajj laws, and the application of taisīr fiqh (facilitative jurisprudence) to encourage balanced worship practices. Practical recommendations include prioritizing first-time pilgrims, implementing health screenings, and fostering a collective understanding of maqāṣid-based priorities. By integrating maqāṣid principles, this research contributes to contemporary Islamic legal discourse, offering a framework for reforming Hajj policies in Indonesia. The proposed approach aims to create a more equitable, sustainable, and socially responsible pilgrimage system, aligned with the higher objectives of Islamic law.